The well-being of farm animals : (Blackwell, 2004)
The Well-Being of Farm Animals: Challenges and Solutions offers veterinarians, veterinary and agriculture students, animal scientists, and food animal producers both practical methods to enhance farm animal well-being, and greater understanding of the theoretical underpinnings of those methods. With a variety of perspectives from respected experts and specialists, this book conveys new research findings and promotes valuable discourse on critical issues. Most importantly, editors Benson and Rollin provide feasible instruction to put theory into practice.